Analysis of the new state financial services holding in Colombia (2020)
The new state entity, Grupo Bicentenario approved by Decree 2111 of 2019, is the third largest financial conglomerate in Colombia, acting as the state bank, made up of a total of eighteen first-tier, second-tier banking companies, insurers, fiduciaries and others, thus strengthening the state financial system, guaranteeing an efficient allocation of resources and contributing to the achievement of financial stability, which will allow it to have greater assistance and coordination for the operation of state-owned companies that are part of the financial sector. and thus optimize its portfolio, thus protecting the assets of Colombians, whose purpose is to provide their financial services to the community, have easy access to financial markets, which should be directed at the working, rural, peasant, and student population, entrepreneurial, micro business, mothers head of household, victim population, ethnic minorities cas and those that are in a vulnerable state.